Yesmeanlicious Pastry / Nurin Yasmin Adlina Mohd Fisal - Nurin Yasmin Adlina, Mohd Fisal (2020)
Yesmeanlicous Pastry was established on 20 February 2020 and aimed on focusing towards Awareness of high quality baked goods is on the rise. Good bread is a rare combination of nutrition, convenience, and luxury. Today's costumers has less time to create wholesome, handmade bread, but increasingly appreciates the nutritional and sensory benefits it provides. Good bread provides fiber and carbohydrates in a convenient, low fat form that is portable and delicious. Good bread never goes out of style. Some of the types of pastries that we sell are really appealing and customers can check out of our menu. Hem and cheese curry puffs are among the most popular menus in our shop. In the curry puff the core is very dense and whole. Melted cheese and hem filling with a mixture of curry aromas make customers feel filled quickly. Additionally, samosa meat curry and hog pretzel bread is one of the menus that we deliver to our customers. Both menus have their own particular specialties. Mini Pavlova was last side dish. This is the food the younger generation is most fond of. This side dish has a sweet taste and is perfect for taking during leisure time. Basically, our target market is for student, teachers and family. We’re looking for students coming to our shop. This is because our pastry shop is situated very close to the colleges, schools and residential areas. It would make our shop easier for customers to come to. The less fortunate can come to our shop to get our pastry at an affordable price as well. Yesmeanlicous pastry marketing strategy is to emphasize the quality and price of our Products. We convince the customers to buy a high qualities pastries which are use of products with high nutrients and fair prices. Are view of our competitors shows that we will be competing against 2 others shop around our location. So, with a good strategy and high quality baking, we believed that we can compete them and make us the best choice for customers to come and buy our products. Our store operates every day starting at 10am to 10pm and at the front of the store we sold our product and at the back of the store ,we have a factory that making the pastry. So,our average sales forecast permonth is RM 53 000 and with one-unit price at RM 4.20.